The Causal Nexus between Public Debt and Economic Growth, A Multivariate Time Series Analysis: Experience from a SAARC Nation (Global Journal of Human-Social Science, 2020)
This research paper enquires about the topicality of the dependence of Bangladesh's economy on public debt. Several authors examined the bearings of public debt and economic growth in different counties and they provided mixed results about the direction of the relation. This study is conducted to find out the causal relationship between public debt and growth from the perspective of Bangladesh's economy, and we use export as a control variable. We excerpted annual time series data from the World Bank website (WDI), IMF, and fiscal year 1986 to2018 data were gathered. One can treat budget deficit as the mother of public debt because the incarnation of the former usually precedents to the creation of the later. Several econometric tools have been behaved as Augmented Dickey-Fuller (ADF), Phillips -Peron (PP), Johansen co integration, Vector error correction model, and Granger casualty to explore short-run causality of public debt on growth.
Keywords: GDP; PUBLIC DEBT; EXPORT; ADF; PP; johansen cointegretion; VECM; granger causality